Stock market analysis through business cycle approach - Dzikevičius, Audrius; Vetrov, Jaroslav (Business: Theory and Practice, 2012)
It is often claimed that stock prices are determined on the basis of some key macroeconomic indicators. Presumably, stock market movements reflect positions taken by market participants based on their assessment about the current state of the economy. Given the forward-looking behaviour of OECD Composite Leading Indicator which identifies business cycle phase, this paper explores the possibility of improving risk-adjusted returns of portfolio of US stocks. Using portfolios which are composed only of US stocks we show that asset weights should be modified to accommodate cyclical shifts in the economy if return/risk efficiency is to be maintained over the full cycle. Monthly data applied were from March 1955 to May 2011.